THE ROLE OF ARABIC IN THE INTEGRATION OF SCIENCE AND TECHNOLOGY - Wulandari, Putri; Siti Rahmadani, Zellyka (Jurnal Al-Hibru, 2025)
This paper aims to determine the role of Arabic in the integration of science and technology, change the perspective that the basis of science comes from Western countries and eliminate the dichotomy of science. Arabic is the language used in scientific books by Muslim intellectuals. Understanding Arabic is the same as diving into pure sources and references for all scientific disciplines. Muslim scholars have played an important role in discovering and exploring science, medicine, mathematics, technology, astronomy, optics, philosophy, education and many other scientific disciplines. The method in this writing uses a qualitative descriptive method with a library research approach and literature study. Data collection by identifying references and reconstructing them from various references such as books, journals and research. The findings of this article reveal, among other things; first, Arabic plays a major role in the development of science and technology; second, Muslim scientists inscribed their valuable findings with gold ink in Arabic and through concrete scientific calculations and rational reasoning; third, Allah Subhanahu wa Ta'ala is the source of all knowledge.